MEDIÇÕES ESPECTROFOTOMÉTRICAS DE SISTEMAS DE JANELA UTILIZANDO LÍQUIDOS TRANSPARENTES (TRANSWALLS) - Piffer, Yuri F.; Mizgier, Martin Ordenes; Marinoski, Deivis L. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper presents the measurement of specular transparent liquid's spectroscopy in the solar wavelength range with normal incidence for Transwall filling purposes. Transwalls can be described as passive solar building's envelope system with direct light gains, but thermal attenuation (spectral selectivity). It has been tested different samples of water, solutions, alcohols and acids, so as float glass 3mm and two prototypes varieties: double glass with internal spacing (gap) of 2mm and 10mm filled with the liquids listed above or empty. All experiments have been carried out in the spectrophotometer Lambda 1050 and compared by Visible Transmittance (Tvis) and Solar Transmittance (Tsolar). Also, Tvis and Tsolar data from 4mm green glass and 12mm Azuria glass have been collected from the National Fenestration Rating Council (NFRC) list for analogy purposes. The results have shown promising spectral selectivity of thin water samples with higher light transmittance than double glass systems and considerable infrared attenuation. Also, the measurements pointed the impact internal reflections can cause to light transmittance when varying from air to water refractive index.